Равномерная оценка семейства энергетических функций для квазилинейных параболических уравнений с сингулярными граничными данными - Евгеньева, Е.А. (Праці Інституту прикладної математики і механіки НАН України, 2017)
Изучение асимптотического поведения решений квазилинейных параболических уравнений в окрестности времени сингулярного обострения граничного режима основано на введении бесконечного семейства энергетических функций, связанных с последовательностью областей пространственно-временных слоев со стремящимися к 0 высотами. Эти энергетические функции удовлетворяют некоторой специальной бесконечной системе дифференциальных неравенств. Анализ свойств этой системы в зависимости от начальных данных, определяемых исходным сингулярным граничным режимом, является одним из ключевых моментов при изучении поведения решений описанной задачи. В работе получена равномерная оценка для решений этих систем при различных граничных режимах, приведено несколько примеров, иллюстрирующих результат. Вивчення асимптотичної поведiнки розв’язкiв квазiлiнiйних параболiчних рiвнянь в околi часу сингулярного загострення граничного режиму засновано на введеннi нескiнченного сiмейства енергетичних функцiй, пов’язаних з послiдовнiстю областей просторово-часових шарiв, висоти яких прямують до 0. Цi енергетичнi функцiї задовольняють деякiй спецiальнiй нескiнченiй системi диференцiальних нерiвностей. Аналiз властивостей цiєї системи в залежностi вiд початкових даних, що визначаються вихiдним сингулярним граничним режимом, є одним з ключових моментiв при вивченнi поведiнки розв’язкiв описаної задачi. У роботi отримана рiвномiрна оцiнка для розв’язкiв цих систем при рiзних граничних режимах, наведено кiлька прикладiв, що iлюструють результат. The purpose of current investigation is to study the asymptotic behavior of solutions of mentioned problem with LS-regime in the neighborhood of blow-up time. In this paper we have obtained some helpful result which will allow us to formed the final estimation for solution profile. The investigation of behavior of solutions is carried out by the method of energy estimations. Singular boundary data generate some estimation for the global energy function associated with the solution of the problem. The method of energy estimations is based on the introduction of an infinite family of energy functions associated with the sequence of domains of space-time layers with height tending to 0. Based on the estimation of global energy function we obtain the system of the differential inequalities for introduced family of energy functions. The main result of the paper is a uniform estimation for these functions. Also there are several examples, which show the dependence between initial energy estimation and final estimation. The result allows us to form an idea of the asymptotic behavior of solution of mentioned problem and it will be used in the future investigation for the obtaining of final estimation.